2020
DOI: 10.1017/s0954579420000942
|View full text |Cite
|
Sign up to set email alerts
|

Emergence and rate of autism in fragile X syndrome across the first years of life

Abstract: Prospective longitudinal studies of idiopathic autism spectrum disorder (ASD) have provided insights into early symptoms and predictors of ASD during infancy, well before ASD can be diagnosed at age 2–3 years. However, research on the emergence of ASD in disorders with a known genetic etiology, contextualized in a developmental framework, is currently lacking. Using a biobehavioral multimethod approach, we (a) determined the rate of ASD in N = 51 preschoolers with fragile X syndrome (FXS) using a clinical best… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
12

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 30 publications
(56 citation statements)
references
References 78 publications
2
42
0
12
Order By: Relevance
“…For example, IBI has been shown to predict later ASD symptoms in a non-linear fashion across age, with greater ASD severity in childhood being associated with longer IBI in infancy but shorter IBI in childhood (57). In the only longitudinal study of ANS function in young children with FXS to date, Roberts and colleagues (41) found that shorter initial IBI, but not developmental change in IBI, predicted later ASD diagnoses in young children with FXS. Interestingly, neither initial RSA nor RSA maturation predicted ASD diagnoses.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…For example, IBI has been shown to predict later ASD symptoms in a non-linear fashion across age, with greater ASD severity in childhood being associated with longer IBI in infancy but shorter IBI in childhood (57). In the only longitudinal study of ANS function in young children with FXS to date, Roberts and colleagues (41) found that shorter initial IBI, but not developmental change in IBI, predicted later ASD diagnoses in young children with FXS. Interestingly, neither initial RSA nor RSA maturation predicted ASD diagnoses.…”
Section: Discussionmentioning
confidence: 99%
“…Roberts et al (57) documented elevated HR and lower RSA in the youngest sample to date (8-40 months of age), and found that lower RSA was associated with greater ASD symptoms in children aged 22 months or older, but not in younger children. In the only longitudinal study to date in FXS, Roberts et al (41) found that shorter initial IBI in infancy, but not change over time, predicted later ASD diagnoses in young children with FXS. Interestingly, neither initial RSA nor change over time in RSA predicted ASD diagnoses.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a rule, autism spectrum disorders are diagnosed at the age of 3–5 years, it is possible to reveal them at 1.5 years and in some cases at 6–12 months; the symptoms are preserved in adolescence and adulthood [ 31 ]. Currently, there are no highly sensitive and specific biological markers of ASD in medicine.…”
Section: Introductionmentioning
confidence: 99%